Copies of the treaties, made 3rd and 21st August, 1871, between Her Majesty the Queen and the Chippewa and Cree Indians of Manitoba and country adjacent [electronic resource]. - Ojibwa Indians. Treaties, etc. 1871.; Cree Indians. Treaties, etc. 1871.; Canada. Treaties, etc. 1871. ([Ottawa? : s.n.], 1872)
Electronic reproduction. Mode of access: Internet. 44